Robust berth scheduling at marine container terminals via hierarchical optimization - Golias, Mihalis; Portal, Isabel; Konur, Dinçer; Kaisar, Evangelos; Kolomvos, Georgios (My University, 2014)
In this paper, we present a mathematical model and a solution approach for the discrete berth scheduling problem, where vessel arrival and handling times are not known with certainty. The proposed model provides a robust berth schedule by minimizing the average and the range of the total service times required for serving all vessels at a marine container terminal. Particularly, a bi-objective optimization problem is formulated such that each of the two objective functions contains another optimization problem in its definition. A heuristic algorithm is proposed to solve the resulting robust berth scheduling problem. Simulation is utilized to evaluate the proposed berth scheduling policy as well as to compare it to three vessel service policies usually adopted in practice for scheduling under uncertainty. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Berth scheduling; Container terminals; Bi-level; Bi-objective; Metaheuristics